2020
DOI: 10.1108/ihr-09-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing consumers' rejection to smartphone transactions in the lodging industry

Abstract: Purpose -The main purpose of this study is to investigate what affects a customer's decision to use the hotel smartphone applications when he/she makes a room reservation. Design/methodology/approach -A total of 266 usable data was collected through an online survey. The research model was tested using confirmatory factor analyses and structural equation modeling.Findings -This study revealed that perceived usefulness, perceived credibility, perceived equipment risk, and perceived change risk affected customer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
3
0
4
Order By: Relevance
“…Even though the literature on digital technology innovations addresses many technical issues (Vermesan and Fries, 2014), business scholars have just begun to examine the impact of these innovations (Ng and Wakenshaw, 2017) on consumer purchases and repurchase intentions, particularly in the hotel industry. For instance, Bae et al (2020) investigate factors that influence the adoption or rejection of digital technologies such as smartphones in the hotel industry. This study utilised the technology adoption model and did not focus on the customer experience.…”
Section: Online Innovation and Repurchase Intentionsmentioning
confidence: 99%
“…Even though the literature on digital technology innovations addresses many technical issues (Vermesan and Fries, 2014), business scholars have just begun to examine the impact of these innovations (Ng and Wakenshaw, 2017) on consumer purchases and repurchase intentions, particularly in the hotel industry. For instance, Bae et al (2020) investigate factors that influence the adoption or rejection of digital technologies such as smartphones in the hotel industry. This study utilised the technology adoption model and did not focus on the customer experience.…”
Section: Online Innovation and Repurchase Intentionsmentioning
confidence: 99%
“…(2017) found that perceived ease of use was not correlated with individuals' attitudes toward using mobile travel apps. Bae et al. (2020) found a positive but insignificant correlation between perceived usefulness and attitude.…”
Section: Discussionmentioning
confidence: 89%
“…However, Weng et al (2017) found that perceived ease of use was not correlated with individuals' attitudes toward using mobile travel apps. Bae et al (2020) found a positive but insignificant correlation between perceived usefulness and attitude. The inconsistency in the findings may be influenced by the economic development level of a country, region, or the study scenario.…”
Section: A Metaanalysis Of Otbs Adoptionmentioning
confidence: 89%
“…Hal ini sejalan dengan pandangan terdahulu yang mengatakan bahwa persepsi kegunaan menekankan manfaat atas penggunaan teknologi diharapkan dapat meningkatkan produktivitas seseorang (Davis, 1989;Ikhsan & Sunaryo, 2020). Hal ini menandakan bahwa ketika individu merasa suatu teknologi bermanfaat bagi kehidupanya cederung mendorong individu untuk menggunakannya (Bae et al, 2020).…”
Section: Kajian Pustaka Persepsi Kegunaan Terhadap Niat Penggunaanunclassified
“…Dengan begitu, kegunaan suatu teknologi menjadi faktor utama dalam mendorong niat individu untuk menggunakan m-payment di masa pandemi Covid-19. Hal ini sejalan dengan penelitian sebelumnya yang mengatakan bahwa persepsi kegunaan memiliki pengaruh yang positif terhadap niat penggunaan teknologi (Bae et al, 2020;Ikhsan & Sunaryo, 2020;H. .…”
Section: Kajian Pustaka Persepsi Kegunaan Terhadap Niat Penggunaanunclassified